PENGARUH KEBIJAKAN ORGANISASI, ANGGARAN, KAPABILITAS SDM DAN KOORDINASI TERHADAP KEBERHASILAN ASSET RECOVERY PADA DIREKTORAT LABUKSI KPK DENGAN KINERJA SEBAGAI VARIABEL MEDIASI - Muhammad Fadli Maududi; Imron HR (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of organizational policies, budgets, human resource capabilities, and coordination on the success of asset recovery at the KPK's Labuksi Directorate, with performance as a mediating variable. This study uses a quantitative approach with the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. Data were obtained through distributing questionnaires to Labuksi Directorate employees involved in tracking, managing, and utilizing assets resulting from corruption. The results show that coordination and human resource capabilities have a positive and significant effect on performance, while organizational policies and budgets do not have a significant effect on performance. Performance is proven to have a significant effect on the success of asset recovery and is a mediating variable that links coordination and human resource capabilities with the success of asset recovery. The R² and Q² values ​​indicate that the model has strong predictive power for the dependent variable, making it suitable for use in explaining organizational effectiveness in the context of asset recovery. These findings indicate that the success of asset recovery is not only determined by the availability of policies or financial resources, but is more determined by the effectiveness of inter-unit coordination and the competence of human resources in carrying out their functions and duties. Therefore, increased synergy, capacity building, and internal policy adjustments are needed to support the optimal performance of the Labuksi Directorate in recovering state assets.